P.138 Corrective Adult Spinal Deformity Procedures in a community hospital: a single institution review. (17th June 2016) - Yuh, S; Warren, M; Frangou, E; Warren, D
Abstract : Background: Adult spinal deformity (ASD) are typically managed in tertiary care centres due to their complexity in surgical planning and peri-operative care.Methods: A retrospective analysis of consecutive corrective ASD surgery performed by a single surgeon at a community based centre performed between 2012 and 2014. Inclusion criteria were age ≥ 18 years with a minimum of 1 year follow-up. We reviewed age, aetiology, mortality, medical and neurological deficit. All standard radiographic deformity parameters were also evaluated and analysed.Results: n=32 corrective spinal deformity procedures were performed. The most common aetiology was de novo degenerative scoliosis. The mean length of stay was 11.94 days. The most common levels fused from T1-pelvis (n=13). L5/S1 was the most common level requiring interbody fusion (n=17). There were n=10 who required a PSO. Only n=4 patients had EBL greater than 3500cc.There were a total of 9 medical complications with post-operative hypotension being the most common (n=3). Hardware failure across the PSO site was the most common long term complication (n=7). There were n=2 death. There were no reported deep infections requiring revisions. Radiographic parameters analysed showed significant improvement.Conclusions: ASD surgery perioperative complication rates in a community hospital are similar to those done in high volume academic centre.